The Sovereignty of the Holy See and Apostolic Nuncios: A Dual Analysis under Canon Law and International Law - SUN Huailiang, (Journal of Research for Christianity in China (JRCC), 2025)
The sovereignty of the Catholic Church is embodied in international law by the Holy See, whose functions and activities are exercised by the Roman Apostolic See. The envoys of the Holy See, also known as Apostolic Nuncios, are charged with consolidating the communion of the Catholic Church in matters of doctrine, liturgy, and organization, as well as regulating and safeguarding the interests of the Church. A precise understanding of the Holy See's sovereignty and the role of the Apostolic Nuncio not only deepens our grasp of the dual legal system unique to Europe but also contributes to the establishment of ideal diplomatic relations between our country and the Holy See.
Keywords: Sovereignty of the Holy See State of Vatican City Roman See Papal Envoy Papal Representative